Air pollution and its impact on human health - B.B. Umarov; SH.B.Xudoyberdiyev; SH.Abdurasulova (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
The article highlights the main sources of atmospheric pollution, its negative impact on human health, and its connection with global environmental problems. Information was also provided on the measures being taken to protect the atmosphere and their effectiveness. This article is intended for students, researchers, and the general public seeking knowledge in the fields of ecology and healthcare.